Novel coding and decoding scheme for modified optical duobinary signal transmission - SHAO Yu-feng; CHEN Lin; WEN Shuang-chun; ZHU Jiang-zhang (Tongxin xuebao)
A novel pre-coding scheme for modified optical duobinary signals was proposed.It could be applied to trans-mit high speed data rate signals（≥ 10Gbit/s）.Through analyzing the process of coding and decoding,It was demon-strated that modified optical duobinary signals have capability in reduction of pulse-to-pulse interaction,and could be di-rectly measured through a conventional binary intensity modulation direct detection（IM-DD） receiver.Two modified op-tical duobinary signals’ formats were simulated to generate.Simulation results show that MD-NRZ and MD-RZ signals’ formats can avoid the eye diagrams’ distortion for long-distance transmission,if the dispersion can be compensated in each amplifier span.Moreover,the MD-RZ signal has lower BER than the MD-NRZ signal after long-distance commu-nication.